Applying Intertextuality on the Translation of Qur’anic Discoursal Meanings - Lecturer: Ghusoon S. Khalil (Journal of College of Education, 2022)
The aim of this study is to examine how intertextuality can be applied as a useful tool to determine the discoursal meanings of the Qur’anic lexical item آنَسَ)) (aanasa) and whether such intertextual nuances of this Qur’anic lexical item have been correctly reflected in some of the translations of the Qur’an. It is hypothesized that no single English verb can be used as an equivalent to the Arabic verb (آنَسَ)(aanasa). Regarding the methodology adopted in this study, the discoursal meanings of the lexical item آنَسَ)) (aanasa) are discussed first, based on different exegeses of the Qur’an and some Arabic dictionaries as well. Then, intertextuality is adopted as a theoretical criterion upon which the discoursal meaning of (آنَسَ) (aanasa) in the Glorious Qur’an is determined. After deciding on the specific discoursal meaning, the study investigates whether the intended discoursal meaning is correctly reflected in the selected translations. It has been found that the translators were inconsistent in some way in their rendition of the Qur’anic lexical item (آنَسَ) (aanasa) due to the fact that they treated each occurrence of that lexical item separately from its other occurrences, and thus were unable to convey the intended meaning. By applying the intertextuality approach, the study concludes that the specific meaning of the Arabic verb (آنَسَ) (aanasa) cannot be rendered into English as a single verb in which the intertextuality nuances can be identified. The paper concludes that the Arabic verb (آنَسَ) (aanasa) can best be translated into English as (to perceive with comfort), (to descry with comfort) or (to discern with comfort); and that this translation should be adopted in interpreting the Glorious Qur’an so as not to distort the intended Qur’anic message. Keywords: Intertextuality, Discoursal Meanings, Qur’anic Lexical Item, Translations of the Qur’an, آنَسَ)) (aanasa)